2015
DOI: 10.1093/jjco/hyv163
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical outcomes between locally advanced hypopharyngeal and oropharyngeal cancer treated with definitive concurrent chemoradiotherapy: implication for subgroup selection for induction chemotherapy

Abstract: Objective: The purpose of this study is to compare the long-term clinical outcome of hypopharynx cancer and oropharynx cancer treated with concurrent chemoradiotherapy. Methods: A total of 213 patients with locally advanced hypopharyngeal squamous cell carcinoma (n = 79) or oropharygeal squamous cell carcinoma (n = 134) were included. All patients were treated with upfront concurrent chemoradiotherapy between 1995 and 2012. Results: The median overall survival and progression-free survival differed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…While the TAX (Cisplatin and Fluorouracil Alone or with Docetaxel in Head and Neck Cancer) 324 trial suggested that TPF IC was superior to a PF regimen with improved survival, we noticed that the 3-year OS rate in the TAX 324 trial, which included about 50% oropharyngeal cancer patients, was 62% in the TPF IC group [6], but only 49% in a subgroup analysis of hypopharynx cancer patients [10]. Such an inferior outcome for hypopharyngeal cancer was similar to our previous study [8] where the 3-year OS rate was 52% in the hypopharynx group compared to 75% in the oropharynx group (HR, 2.21; 95% CI, 1.38 to 3.56; p = 0.001) after treatment with upfront CRT. Hypopharynx and BOT cancers have been regarded as good candidates for organ preservation, and so multidisciplinary treatments including chemotherapy, and radiotherapy rather than surgery have been evaluated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While the TAX (Cisplatin and Fluorouracil Alone or with Docetaxel in Head and Neck Cancer) 324 trial suggested that TPF IC was superior to a PF regimen with improved survival, we noticed that the 3-year OS rate in the TAX 324 trial, which included about 50% oropharyngeal cancer patients, was 62% in the TPF IC group [6], but only 49% in a subgroup analysis of hypopharynx cancer patients [10]. Such an inferior outcome for hypopharyngeal cancer was similar to our previous study [8] where the 3-year OS rate was 52% in the hypopharynx group compared to 75% in the oropharynx group (HR, 2.21; 95% CI, 1.38 to 3.56; p = 0.001) after treatment with upfront CRT. Hypopharynx and BOT cancers have been regarded as good candidates for organ preservation, and so multidisciplinary treatments including chemotherapy, and radiotherapy rather than surgery have been evaluated.…”
Section: Discussionsupporting
confidence: 89%
“…We hypothesized that some subgroup populations could benefit from integrating IC into CRT alone. Previously, we confirmed that long-term outcome was significantly worse in patients with hypopharyngeal cancer compared to those with oropharyngeal cancer (3-year overall survival [OS] rate 52% vs. 75%, p = 0.001; 3-year progression-free survival [PFS] rate 42% vs. 72%, p < 0.001), although the overall response rate (ORR) after CRT was fairly good in both groups [8]. And another phase III trial comparing concurrent CRT versus IC followed by CRT reported a more pronounced benefit of IC with a TPF regimen in patients with non-oropharyngeal cancer compared to overall LASCC patients [9].…”
Section: Introductionsupporting
confidence: 52%
“…Bozec noted that those patients who responded to induction chemotherapy were more likely to require permanent enteral nutrition . Lim recorded a 3‐year progression‐free survival of 42% with concurrent CRT, worse than, with comparable treatment, at other head and neck sites . This series had worse outcomes for those treated with chemotherapy; however, this was for a group who had many adverse features at presentation.…”
Section: Discussionsupporting
confidence: 79%
“…32 Lim recorded a 3-year progression-free survival of 42% with concurrent CRT, worse than, with comparable treatment, at other head and neck sites. 33 This series had worse outcomes for those treated with chemotherapy; however, this was for a group who had many adverse features at presentation. There are other determinants of achieving local control.…”
Section: Figurementioning
confidence: 83%
“…Carcinoma of the hypopharynx is associated with poor survival, largely because tumors in this region remain asymptomatic until the disease reaches an advanced stage [ 1 , 2 ]. Stage III or IV hypopharyngeal cancer often invades the cervical esophagus, which is a very aggressive cancer with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%